The effect of physical exercise in increasing hypoxia-inducible factor-1 alpha: a systematic review - Yulfadinata , A.; Ayubi , N.; Wibawa , J.C.; Rizki, A.Z.; Afandi, A.; Jr , P.B.D. (Medicni Perspektivi, 2025)
The human body during physical exercise triggers various molecular reactions, one of which is the activation of hypoxia-inducible factor-1 alpha (HIF-1α), a transcription factor that plays a role in cellular responses to hypoxic conditions. Hypoxia is a condition in which the body experiences a lack of oxygen. Although it is known that physical exercise can increase HIF-1α expression, until now there is still inconsistency in the results of studies related to the impact of physical exercise on HIF-1α expression.In addition, the underlying mechanism of increased HIF-1α during physical exercise is not fully understood. The lack of a deep understanding of the causal relationship between physical exercise and HIF-1α expression is a challenge in efforts to unravel the underlying mechanisms. Therefore, more systematic studies are needed to evaluate the specific effects of physical exercise on HIF-1α regulation and its impact on physiological adaptation. The aim of this study was to investigate and measure the mechanism of physical exercise on increasing the expression of hypoxia-inducible factor 1-alpha (HIF-1α). Several journal databases, including Embase, Pubmed, Web of Science, and Scopus, were searched for this study. The study considered several criteria, including studies published in the last five years and those related to erythropoietin, physical activity, and HIF-1α. The only papers excluded from inclusion in this analysis were those published in non-reputable journals.Using databases from Embase, Web of Science, Pubmed, and Scopus, a total of 1578 publications were identified. Ten carefully screened and peer-reviewed papers addressed what is needed for this systemic change. The current standard operating procedure for investigations was established using Systematic and Meta-Analysis Preferred Reporting Items (PRISMA). The results of this systemic analysis show that physical exercise has been shown to increase HIF-1α expression. Increased HIF-1α causes the hormone erythropoietin to be secreted and an increase in erythrocytes count which then affects hemoglobin and VO2max and ultimately increases the athlete's physical performance.